A novel process of chemical mechanical polishing for FV520B steel. (November 2020) - Liao, Longxing; Zhang, Zhenyu; Liu, Jie; Li, Yubiao; Cui, Xiangxiang; Liu, Lu
Abstract: In this study, a novel process of chemical mechanical polishing (CMP) is proposed for FV520B steel. A novel environmentally friendly CMP slurry without any strong acids, alkalis, or hazardous chemicals is developed. The slurry consists of hydrogen peroxide (H2 O2 ), nicotinic acid, nonylphenol ethoxylate, and deionized water. This is different from the traditional milling processes, which is a stress removal process, resulting in obvious scratches. In comparison, the developed CMP process combines the advantages of chemical dissolution and mechanical abrasion to obtain a smooth surface of FV520B steel with a surface roughness Ra of 5.7 nm. Single-factor experiments are used to explore the optimal polishing composition and time of the CMP slurry. Then, the orthogonal experiments are designed to find the optimal process parameters, such as the polishing pressure, the rotational speed of the polishing pad, and the sizes and concentration of abrasives. Also, the effects of various parameters on the surface roughness and material removal rate are analyzed by the range method. This study provides a new pathway of processing high-performance FV520B steel components.